TURKEY'S ISLAMISTS: FROM POWER-SHARING TO POLITICAL INCUMBENCY - (:unkn) unknown (TURKISH POLICY QUARTERLY, 2015)
The complex relationship between political Islam and the Turkish state - from political exclusion in the early Republican era, to power-sharing in the post-World War II multi-party era, to political incumbency in the 2000s - was crowned by AKP's landslide electoral victory in 2002. The author debunks two myths regarding this relationship: first, that Kemalism enjoyed a monopoly of political power for decades and second, that Islamists achieved victory in 2002 after being the regime's sole opposition. According to the author, Turkey's failed Middle East policy can be attributed to AKP's misconception that its Islamic counterparts would achieve power after the Arab uprisings just as they had done in Turkey in 2002.